El comercio rioplatense y la construcción discursiva de un espacio político por el cabildo de Buenos Aires, 1610-1660 - Amadori, Arrigo (2015)
This article proposes an approach to the integration of the city of Buenos Aires within the trade flow which connected the Atlantic area with the Viceroyalty of Peru, through a political-cultural analysis of the relationship between a peripheral space and the Crown, which lends meaning and legitimacy to the failure to comply with royal provisions and to the successive requests by local powers to bring about the commercial opening of the port. Specifically, we address the problem of building a political discourse at the heart of the cabildo of Buenos Aires, between the years 1610 and 1660, through which was revealed a conceptualization of the enclave, of its relationship with the Crown and of its function within a larger political body.